1999
DOI: 10.1046/j.1365-2796.1999.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial medicine – recent advances

Abstract: Abstract. Graff C, Clayton DA, Larsson N-G (Center for Molecular Medicine, Karolinska Hospital, Stockholm, Sweden, and Howard Hughes Medical Institute, Chevy Chase, MD, USA). Mitochondrial medicine 2 recent advances (Review). J Intern Med 1999; 246: 11223.Mitochondria contain the respiratory chain enzyme complexes that carry out oxidative phosphorylation and produce the main part of cellular energy in the form of ATP. Mitochondrial DNA (mtDNA) encodes essential subunits of the respiratory chain and is thus cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 105 publications
0
21
0
2
Order By: Relevance
“…This process occurs in mitochondria in which mitochondrial (mt)DNA encodes for essential subunits of the respiratory chain (20,55). Even under physiological conditions, there are large variations in the number of deletions in mtDNA due to its specific structure, function, and location.…”
Section: Epithelium; Energy Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This process occurs in mitochondria in which mitochondrial (mt)DNA encodes for essential subunits of the respiratory chain (20,55). Even under physiological conditions, there are large variations in the number of deletions in mtDNA due to its specific structure, function, and location.…”
Section: Epithelium; Energy Metabolismmentioning
confidence: 99%
“…mtDNA mutates 10 times as frequently as nuclear DNA, has no protective histones or repair system, and is constantly exposed to free radicals generated during the cell's normal oxidative phosphorylation process (25,26). When mtDNA mutations occur in muscle or nerve cells, this results in reduced energy production translated into obvious clinical manifestations (20,55). However, similar defects may be far more difficult to detect when they occur in the intestinal epithelium, particularly under inflammatory conditions.…”
Section: Epithelium; Energy Metabolismmentioning
confidence: 99%
“…Myopathies, neuropathies, encephalomyopathies and many other diseases have been associated with mutations in the mitochondrial DNA (mtDNA). In many of these diseases onset of clinical symptoms is late, occurring as the ratio of mutant to wildtype mtDNA passes a critical threshold depending on energy demands of the particular tissue (Graff et al, 1999;Nakada et al, 2001a). Recent studies of the effect of mtDNA mutations on disease phenotypes in a transgenic mouse model (Inoue et al, 2000;Nakada et al, 2001a;Nakada et al, 2001b;Nakada et al, 2001c;Shoubridge, 2000) suggested an important protection mechanism against the onset of disease symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of mtDNA cause several genetic syndromes with deficient oxidative phosphorylation and have also been implicated in common age-associated disorders, e.g., heart failure, diabetes mellitus, and neurodegeneration (3)(4)(5). The mtDNA mutation disorders are extremely pleiotropic, and affected patients may have symptoms from almost any organ with varying ages of onset (6).…”
mentioning
confidence: 99%